Herbicide absorption and translocation by Eurasian watermilfoil and hydrilla - Vassios, Joseph D., author; Nissen, Scott, advisor; Westra, Philip, committee member; Shaner, Dale, committee member; Meiman, Paul, committee member (Colorado State University. Libraries, 2012)
Hydrilla and Eurasian watermilfoil are submersed invasive species that occur commonly across the US. These species are aggressive competitors, and form dense, monotypic stands. Dense stands of these species form mats on the surface, and impact water flow, as well as the economic and ecological value of water bodies. With the severe impact of these species, many control methods have been implemented to restore value to infested areas. The systemic herbicides fluridone, penoxsulam, and triclopyr are registered for aquatic use. While all three herbicides can be used for Eurasian watermilfoil control, only fluridone and penoxsulam can be used for hydrilla. The rates and selectivity for these herbicides have been documented, but little work has been completed to characterize their absorption and translocation in submersed aquatic species. The goals of this research were to (1) evaluate herbicide absorption and translocation following shoot exposure, (2) evaluate herbicide absorption and translocation following root exposure, and (3) evaluate triclopyr absorption and translocation in Eurasian watermilfoil following liquid and granular treatments. Previous work established linear relationships between herbicide lipophilicity (as determined by log KOW) and bioaccumulation in both terrestrial and aquatic species. Based on the differences in lipophilicity among the three herbicides tested (fluridone>>penoxsulam>triclopyr) we expected fluridone to accumulate the most in these species, with significantly lower accumulation of penoxsulam and triclopyr. Bioaccumulation following root exposure followed this trend, with significantly greater fluridone accumulation than penoxsulam or triclopyr; however, following shoot exposure, triclopyr accumulation was greatest in both species 192 HAT, followed by fluridone and penoxsulam. Overall accumulation was similar for both species following root exposure, but accumulation following shoot exposure was approximately three times greater for Eurasian watermilfoil. Translocation was limited following both root and shoot exposures. The translocation following root treatment was greater than shoot treatment in nearly all cases, with up to 27% of absorbed herbicide present in shoots 192 HAT. Translocation following shoot treatment showed a maximum of 12.5% of absorbed herbicide present in roots 192 HAT. These findings are consistent with previous work that indicated there was more acropetal than basipetal translocation in submersed species. There were no significant differences in overall absorption by Eurasian watermilfoil following liquid and granular triclopyr treatments; however, differences were observed between plant parts. Apical meristems accumulated the most triclopyr following liquid treatment, and root accumulation was greatest following granular treatment. Distribution at the whole plant level resulted in 11 times more herbicide in roots following granular treatment when compared to the liquid treatment. These results indicate that granular formulations may provide better control of Eurasian watermilfoil roots, compared to an equal rate of a liquid formulation.
Keywords: absorption; herbicide; translocation; weed; Eurasian watermilfoil; Hydrilla